2003
DOI: 10.1128/aem.69.7.4177-4182.2003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pulsed-Field Gel Electrophoresis To Characterize the Heterogeneity and Clonality ofSalmonellaIsolates Obtained from the Carcasses and Feces of Swine at Slaughter

Abstract: Salmonella enterica isolates were recovered from swine at a collaborating processing plant over a 2-month period in the spring of 2000. In the present study, molecular subtyping by pulsed-field gel electrophoresis (PFGE) was performed on the 581 confirmed Salmonella isolates from the 84 Salmonella-positive samples obtained from the previous study. A total of 32 different PFGE pulsotypes were observed visually, and a BioNumerics software analysis clustered those pulsotypes into 12 PFGE groups. The B, F, and G g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…enterica serovar (Copenhagen) DT104 has been extensively studied with XbaI restriction (5,7,10,14,17). The published subtypes for DT104 were or nearly were identical to the patterns found in our database.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…enterica serovar (Copenhagen) DT104 has been extensively studied with XbaI restriction (5,7,10,14,17). The published subtypes for DT104 were or nearly were identical to the patterns found in our database.…”
Section: Discussionsupporting
confidence: 52%
“…It was found that the same bands mentioned above were conserved. Wonderling et al (17) used the same analysis program and parameters as those of this study. Their results showed grouping of serotypes by their XbaI PFGE subtypes with cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A low frequency (2.7%) of ST isolates resistant to ciprofloxacin was reported in Taiwan from 1996 to 2001 (Hsueh et al, 2004), whereas our study and other previous studies identified no ST isolates that were resistant to ciprofloxacin (Gorman and Adley, 2004;Gross et al, 1998). Salmonella isolates from cattle and turkey are more often multi-drug resistant (MDR) than isolates from other species (Wonderling et al, 2003). The rate of MDR against >2 antimicrobial agents was 100% in cattle, 77.3% in pigs and 47.6% in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis PFGE analysis was conducted according to the methods of Tenover et al (1995) and Wonderling et al (2003), with some modifications. Macro-restriction patterns were analyzed with BioNumerics software (Applied-Maths, Sin-Martens-Latem, Belgium) and banding patterns were compared using Dice coefficients with a 1% band position tolerance.…”
Section: Pulsed-field Gel Electrophoresismentioning
confidence: 99%
“…The bacterial isolates were fingerprinted by the XbaI-PFGE method, using the PulseNet protocol developed by the CDC (22). The gel images were processed and analyzed by BioNumerics software.…”
Section: Bacterial Isolatesmentioning
confidence: 99%